2021
DOI: 10.1183/13993003.04474-2020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic respiratory diseases are predictors of severe outcome in COVID-19 hospitalised patients: a nationwide study

Abstract: BackgroundInfluenza epidemics were initially considered to be a suitable model for the COVID-19 epidemic, but there is a lack of data concerning patients with chronic respiratory diseases (CRD), who were supposed to be at risk of severe forms of COVID-19.MethodsThis nationwide retrospective cohort study describes patients with prior lung disease hospitalised for COVID-19 (March-April 2020) or influenza (2018–2019 influenza outbreak). We compare the resulting pulmonary complications, need for intensive care and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 48 publications
5
91
0
2
Order By: Relevance
“…A systematic review and meta-analysis analyzing over 690,000 patients with chronic lung conditions with COVID-19 infection showed that chronic lung conditions significantly increase the odds of poor clinical outcomes in patients with COVID-19: increased odds of hospitalization (odd ratio 4.23, 95% CI, 3.65-4.90), ICU admission (odd ratio 1.35, 95% CI 1.02-1.78), and mortality (odd ratio 2.47, 95% CI 2.18-2.79) [99]. Patients with chronic respiratory diseases (CRD) such as chronic obstructive pulmonary disease, bronchiectasis, cystic fibrosis, and interstitial lung disease have higher risks for severe COVID-19 hospital admissions and mortality risk [100]. The risk of COVID-19 patients developing ventilator-associated pneumonia and pulmonary embolism is higher than patients with influenza.…”
Section: Chronic Respiratory Diseasesmentioning
confidence: 99%
“…A systematic review and meta-analysis analyzing over 690,000 patients with chronic lung conditions with COVID-19 infection showed that chronic lung conditions significantly increase the odds of poor clinical outcomes in patients with COVID-19: increased odds of hospitalization (odd ratio 4.23, 95% CI, 3.65-4.90), ICU admission (odd ratio 1.35, 95% CI 1.02-1.78), and mortality (odd ratio 2.47, 95% CI 2.18-2.79) [99]. Patients with chronic respiratory diseases (CRD) such as chronic obstructive pulmonary disease, bronchiectasis, cystic fibrosis, and interstitial lung disease have higher risks for severe COVID-19 hospital admissions and mortality risk [100]. The risk of COVID-19 patients developing ventilator-associated pneumonia and pulmonary embolism is higher than patients with influenza.…”
Section: Chronic Respiratory Diseasesmentioning
confidence: 99%
“…To further appraise the impact of potential baseline confounders, a meta-regression analysis using age, gender, HT, DM, chronic pulmonary disease and hyperlipidaemia as moderator variables was performed. These variables were selected since previous analyses have identified those comorbidities as independent predictors of mortality in COVID-19 patients [2,3,10,11]. All meta-analyses were conducted using Comprehensive Meta-Analysis software, version 3 (Biostat, Englewood, NJ, USA).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Patients with respiratory diseases are considered at high risk of developing severe COVID-19 [ 1 ], and this is true also for CF patients for whom higher incidence and hospitalization rates were documented as compared to the age-matched general population [ 2 ].…”
Section: Introductionmentioning
confidence: 99%